Fiscal Reforms That Work. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
Reducing the budget deficit is not easy. Keynesian theory suggests thatlowering government expenditures and raising revenues can lead to afalloff in economic activity. This paper argues the neoclassical approach - that a firm and credible reduction in expenditures, by engendering confidence that taxes will be less burdensome in the future,may lead to lower interest rates, boost consumption, and increaseinvestment spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet